2008
DOI: 10.1029/2007jf000920
|View full text |Cite
|
Sign up to set email alerts
|

Triggering and drainage mechanisms of the 2004 glacier‐dammed lake outburst in Gornergletscher, Switzerland

Abstract: [ 1 ] To investigate the triggering and the drainage mechanisms of ag lacier-dammed lake outburst, we conducted high-frequency measurements of the ice surface motion in the vicinity of Gornersee, an ice marginal lake on Gornergletscher,S witzerland. During the outburst event in July 2004, the ice surface within ad istance of 400 mf rom the lakeshore moved vertically upward by up to 0.1 m. This vertical surface motion cannot be explained by vertical straining of ice which was measured in one of the boreholes; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 39 publications
5
64
1
1
Order By: Relevance
“…The subglacial volume ( VnormalS) at the beginning of the record was 4.0 (1.7–5.6) ×106 m 3 and increased to a maximum of 20.8 (14.3–22.6) ×106 m 3 on 20 August, three days after the lake level maximum. This lag between peak lake level (i.e., VnormalA) and maximum uplift of the shelf (i.e., VnormalS) has also been observed during outburst floods at other sites (e.g., Anderson et al, ; Sugiyama et al, ). The highest inferred daily discharge rate from the subaerial and subglacial reservoirs is 65 m 3 s 1 (Figure S3), which occurred on 4 September, though we note that no estimates of subaerial volume are available on 5 and 6 September, after the lake level dipped below the sensor elevation.…”
Section: Resultsmentioning
confidence: 61%
“…The subglacial volume ( VnormalS) at the beginning of the record was 4.0 (1.7–5.6) ×106 m 3 and increased to a maximum of 20.8 (14.3–22.6) ×106 m 3 on 20 August, three days after the lake level maximum. This lag between peak lake level (i.e., VnormalA) and maximum uplift of the shelf (i.e., VnormalS) has also been observed during outburst floods at other sites (e.g., Anderson et al, ; Sugiyama et al, ). The highest inferred daily discharge rate from the subaerial and subglacial reservoirs is 65 m 3 s 1 (Figure S3), which occurred on 4 September, though we note that no estimates of subaerial volume are available on 5 and 6 September, after the lake level dipped below the sensor elevation.…”
Section: Resultsmentioning
confidence: 61%
“…This lowering is simultaneous with uplift at GPS NW, GPS SE and GPS NE, suggesting that the water delivered to the bed during rapid discharge did not access the bed beneath GPS SW. Finally, at 03:00 when GPS SW moves north up the bed slope there is a second low magnitude (10 cm) period of uplift exclusive to GPS SW. Sugiyama et al (2008) observed the greatest uplift near to the drainage centre during the subglacial drainage of icemarginal lake Gornersee in Switzerland and we therefore assert, like Das et al (2008), that surface uplift was likely greater near the centre of the lake. The highest-magnitude uplift observed in this study of 0.9 m by GPS NW is the most consistent with the 1.2 m of uplift measured by Das et al. The bed slope underneath GPS NW slopes down towards the north-west (Fig.…”
Section: Vertical Ice Surface Motionmentioning
confidence: 99%
“…In recent field observations on an Alpine glacier (Gornergletscher, Switzerland), repeated near-reversal of flow, accompanied by reversed displacement direction was observed (Sugiyama et al, 2007(Sugiyama et al, , 2008. The change of motion takes place within a few days during the periodical drainage of a supra-glacial lake, and is possibly related to the unloading and stress redistribution during the rapid drainage.…”
Section: Introductionmentioning
confidence: 99%